Efectos secundarios, al consumo de sustancias y medicamentos para prolongar la vigilia, en los estudiantes del tercer ciclo de la Carrera de Medicina de la Universidad Nacional de Loja, en el periodo marzo-julio 2014 - Herrera Aguirre, Liliana Elizabeth (2015)
In the present research work it is to determine the existence of substance and drugs to prolong wakefulness in students studying Human Medicine; identify and classify substances consumed; and determining the intake side effects. The study design was descriptive qualitative and quantitative cross section. The sample was constituted 100% of the students enrolled in the third cycle race of Human Medicine of the National University of Loja, which corresponded to 83 students, who prior authorization of the Governing Area Human Health accepted participate in an anonymous survey and structured. This study showed that 59.1% ingested energizing, coffee 55.7% and coke 19.0%; Side effects that occurred more frequently was excessive sleep increased by 21.7% and 14.8% for nausea. 31.3% of the population self-medicate possessing stimulant as active ingredient at Modafinil, presenting side effects such as headache 19.6%, 15.8% and sleep. It was observed that if there is substance consumption of energy and stimulant medications to prolong wakefulness, stimulating consumption exceeds half the population and medicines has a lower percentage; substances with higher intake were coffee and coca-cola on the other hand consumed medicines are composed of modafinil; Side effects that occurred were sleeping, nausea and headache. Keywords: substances, drugs, waking, students, energizers, stimulants, side effects.